The ether-linked lipids of rat epididymis are affected by mild hyperthermia - Luquez, Jessica Mariela (2016)
It is widely known that heat stress temporarily suppresses spermatogenesis in the mammalian testis, but the impact on the epididymis is barely known. The aim of this study was to examine the effects of short, repeated once-a-day episodes of hyperthermia (43ºC) on the ether-linked glycerophospholipids (GPL) and triglycerides (TG) of rat epididymis. One-week post-treatment, the expression (mRNA) of alkylglycerone phosphate synthase (AGPS), a key peroxisomal enzyme in the synthesis of these lipids, significantly fell in caput and corpus epididymis. Coincidentally, levels of the plasmalogen precursor, plasmanyletanolamine, decreased. Concurrently, plasmenylethanolamine and plasmenylcholine accumulated in caput, ascribable to injured and motionless cells and sperm collecting in the lumen. Catabolism of such GPL had started in the epididymal epithelium, as suggested by the build-up of ether-linked TG. Between weeks 2 and 6, spermatogenesis restarted in the testis. Although the epididymis was still sperm-free at week 6, its levels of ether-linked GPL and TG were much higher than those of untreated controls, in agreement with the recovery of AGPS expression. Ether-linked TG were formed by de novo synthesis and during GPL breakdown. The presence of spermatozoa in the epididymal lumen apparently plays a regulatory role in the biosynthesis of ether-linked lipids by the epididymal epithelium